2011
DOI: 10.1002/pip.1108
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced infrared transmission of GZO film by rapid thermal annealing for Si thin film solar cells

Abstract: Ga doped ZnO (GZO) films prepared by sputtering at room temperature were rapid thermal annealed (RTA) at elevated temperatures. With increasing annealing temperature up to 570°C, film transmission enhanced significantly over wide spectral range especially in infrared region. Hall effect measurements revealed that carrier density decreased from ∼8 × 1020 to ∼ 3 × 1020 cm−3 while carrier mobility increased from ∼15 to ∼28 cm2/Vs after the annealing, and consequently low film resistivity was preserved. Hydrogenat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…In an ideal case and in the limit of very weak absorption, the optical path length inside a dielectric slab is enhanced by a factor of 4 n 2 , where n is its refractive index . In the superstrate configuration, surface textures are incorporated into solar cells mostly by using textured TCO films: CVD‐grown FTO, CVD‐grown ZnO:B (BZO), and etched ZnO:Al (AZO) or ZnO:Ga (GZO) . The former two films possess random pyramidal textures, whereas the latter films have crater‐like holes obtained by the chemical etching of sputtered films, as shown in Figure (a)–(c).…”
Section: Device Designmentioning
confidence: 99%
“…In an ideal case and in the limit of very weak absorption, the optical path length inside a dielectric slab is enhanced by a factor of 4 n 2 , where n is its refractive index . In the superstrate configuration, surface textures are incorporated into solar cells mostly by using textured TCO films: CVD‐grown FTO, CVD‐grown ZnO:B (BZO), and etched ZnO:Al (AZO) or ZnO:Ga (GZO) . The former two films possess random pyramidal textures, whereas the latter films have crater‐like holes obtained by the chemical etching of sputtered films, as shown in Figure (a)–(c).…”
Section: Device Designmentioning
confidence: 99%
“…8,[18][19][20] For the thin films deposited at low substrate temperatures with a poor crystalline quality, these defects could act as the optical absorption centers and decrease the transmission in the UV and visible regions. 11,19 The increase in the average transmittance in the UV and visible regions after RTA indicated that the defect density was strongly reduced via RTA. The reduction in the defect density led to an increase in the carrier concentration and the Hall mobility.…”
Section: Optical Propertiesmentioning
confidence: 96%
“…They found that the resistivity decreased and the mobility increased as the annealing temperature increased, and with improved crystallinity. 10 Jia et al 11 found that RTA treatment could improve the GZO thin film transmission significantly without deterioration of the film conductivity after annealing at 570°C. Despite RTA treatment having been successfully applied in improving the properties of ZnO-based thin films, few studies on the effects of RTA treatment on the electrical transport properties of AZO and GZO thin films deposited at different temperatures can be found in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome this problem, a number of light trapping techniques have been investigated that aim at light manipulation inside the absorber layers, increasing the effective path length in the cell [4][5][6][7][8]. The most widely used techniques are the natural growth of transparent conductive oxide (TCO) textures by atmospheric pressure chemical vapor deposition (APCVD) of F-doped SnO 2 [4], low pressure chemical vapor deposition (LPCVD) of B-doped ZnO (BZO), or wet-etching preceded by sputtering of Al-or Ga-doped ZnO [5][6][7][8]. However, it remains difficult to effectively scatter solar radiation along a broad wavelength range; in particular, in the long wavelength region, given the small feature sizes of the textured interface.…”
Section: Introductionmentioning
confidence: 99%
“…Although the micromorph tandem solar cell (a combination of an amorphous (a-Si:H) high band-gap top cell and a microcrystalline (c-Si:H) low band-gap bottom cell) is one of the most promising candidates in terms of power conversion efficiency [2], the intrinsic poor light absorption of silicon in the long wavelength range restricts further improvement of the cell performance via the multi-junction approach [3]. To overcome this problem, a number of light trapping techniques have been investigated that aim at light manipulation inside the absorber layers, increasing the effective path length in the cell [4][5][6][7][8]. The most widely used techniques are the natural growth of transparent conductive oxide (TCO) textures by atmospheric pressure chemical vapor deposition (APCVD) of F-doped SnO 2 [4], low pressure chemical vapor deposition (LPCVD) of B-doped ZnO (BZO), or wet-etching preceded by sputtering of Al-or Ga-doped ZnO [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%